Inhibition of spore germination and mycelial growth of three fruit rot pathogens using some chemical fungicides and botanical extracts - Begum, Most. Ferdousi; Mahal, Mst Ferdowsi; Alam, Md Shahidul (Journal of Life and Earth Science, 2011)
Six chemical fungicides and extracts of 15 locally available plants were tested against three fruit rot pathogens viz. Fusarium oxysporium f. sp. capsici, Rhizopus artocurpi and Alternaria tenuis for the evaluation of inhibition of spore germination and mycelial growth. Among the fungicides tested, all the concentrations of Ridomil showed 100% inhibition of spore germination and the least inhibition was recorded in case of treatment with Bavistin for F. oxysporium f. sp. capsici. In case of R. artocarpi and A. tenuis, Dithene–M 45 showed good inhibitory effects but Thiovit had no inhibitory effect against A. tenuis. Both leaf and seed extracts of Azadirachta indica showed good inhibitory effect than tested with other plant extracts. Moringa oleifera extract showed least inhibitory effect against all the fungi tested. Datura metel, Plygonum oriantale, Tagestes patula and Micania scandens also showed promising inhibition on spore germination and mycelial growth of all the pathogens tested. Key words: Fruit rot pathogens; plant extracts; chemical fungicides; spore germination; mycelial growth; PIGR DOI: 10.3329/jles.v5i0.7344 J. Life Earth Sci., Vol. 5: 23-27, 2010